Morphometric examination of the paranasal sinuses and mastoid air cells using computed tomography - Karakas, S; Kavakli, A (K Faisal Spec Hosp Res Centre, 2005)
Background: The paranasal sinuses and mastoid air cells vary considerably in size and shape from person to person. The main structures are pneumatic. In this study, we investigated the relationship between right and left sides and evaluated the volume changes according to age and sex. Methods: Of all patients attending the radiology department, 91 cases without paranasal sinuses and mastoid air cells pathology (i.e., inflammation, operation or trauma) were selected for evaluation. Axial computed tomography (CT) scans were obtained for both paranasal sinuses and temporal bones. In all scans, the volumes of each area (maxillary sinus, frontal sinus, sphenoid sinus and mastoid air cell) were calculated and analyzed statistically. Results: The volumes of paranasal sinuses and mastoid air cells increased with age and women had a lower mean volume. There was a positive correlation between right-left and ipsilateral structures (paranasal sinuses and mastoid air cells). Conclusions: These results are helpful in understanding the normal and pathological conditions of the paranasal sinuses and the mastoid air cells.
Keywords: Para-Nasal Sinuses; Sphenoid Sinus; Pneumatization; Volume; Ct; System; Size; Area